(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2005)
Spreading, conditions and causes of formation of landslides in Armenia, their varieties, intensity of displacement, peculiarities of landslide formations from the point of view of lithology etc. are examined. Maximum of their prevalence is marked in high-altitude interval of 2000-1500 m and lower. Their seismogenic varieties, adjacent to the active fault zones, are particularly distinguished among the landslides of Armenia. Great attention is paid to the role of anthropogenic factor in landslide formation in the Republic.